Publikasi Artikel Ilmiah sebagai Kebutuhan Berprestasi Mahasiswa: Studi Kasus Kelas Menulis FUSA UIN Mataram - Wahyudin Darmalaksana; Putri Anditasari; Hidayatul Fikra; Susanti Vera; Fitriani Fitriani (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to discuss the need for achievement in the student environment in the publication of scientific articles through the formation of the